2016
DOI: 10.1371/journal.pone.0146932
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Feeding in Newborn Dairy Calves Cannot Compensate Colostrum Deprivation: Study on Metabolic, Antioxidative and Inflammatory Traits

Abstract: Immaturity of the neonatal immune system is causative for high morbidity in calves and colostrum intake is crucial for acquiring passive immunity. Pathogenesis is promoted by reactive oxygen species accumulating at birth if counter-regulation is inadequate. The flavonol quercetin exerts antioxidative and anti-inflammatory effects that may enhance neonatal health. The aim of this work was to study effects of quercetin feeding on metabolic, antioxidative and inflammatory parameters in neonatal calves to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 67 publications
2
28
0
Order By: Relevance
“…In contrast, immunoglobulin concentrations in formula-fed calves remained low until the end of the experiment. The immunoglobulin intake was also reflected by the total plasma protein concentration, as shown in previous studies (Rauprich et al, 2000;Gruse et al, 2016). The intention of the prophylactic treatments in formula-fed calves was to compensate for the lack of immunological protection by colostrum feeding.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In contrast, immunoglobulin concentrations in formula-fed calves remained low until the end of the experiment. The immunoglobulin intake was also reflected by the total plasma protein concentration, as shown in previous studies (Rauprich et al, 2000;Gruse et al, 2016). The intention of the prophylactic treatments in formula-fed calves was to compensate for the lack of immunological protection by colostrum feeding.…”
Section: Discussionmentioning
confidence: 69%
“…Plasma concentrations of IgG1, IgG2, and IgM (all Ig were not measured postprandially on d 9) were determined via ELISA (no. E10-116, E10-101, E10-117, Bethyl Laboratories Inc., Montgomery, TX; Gruse et al, 2016). The intra-and interassay coefficients of variation were 3.1% and 2.7% for IgG1, 2.8% and 1.7% for IgG2, and 4.2% and 2.9% for IgM.…”
Section: Blood Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the plasma IgM concentration showed a second peak in plasma after the first weeks of age and this peak may reflect antigenic stimulation by environmental antigens. Recent findings in colostrum-deprived calves showed that calves exhibit indigenous IgM production during the first week of life [58]. Although statistically not significant, the lower plasma IgG1 concentration in ADLIB between days 36 and 57 indicates that antigenic stimulation in this group was on a lower level and the risk for infection or antigenic stimulation was obviously reduced in this group after first month of life.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study one ADLIB calf with elevated plasma haptoglobin had loose feces during second week of life and possibly suffered from a bacterial infection [62]. An increased haptoglobin concentration was recently measured only in colostrum-deprived calves during first week of life [58]. …”
Section: Discussionmentioning
confidence: 93%